PENGARUH CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN: INTELLECTUAL CAPITAL SEBAGAI VARIABEL INTERVENING (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2012-2014) - Alexander Kristianto Wasisto; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2016)
The purpose of this research is to analyze the influence of corporate governance with company performance through intellectual capital. Variables of this research are board size, board independence, board of director, managerial ownership, institutional ownership as independen variable, intellectual capital as intervening variable and company performance as dependend variable.The sample consists of 129 companies listed in the Indonesia Stock Exchanged (IDX) period 2012-2014 and provide all the data writer’s need. The data that was used in this research was secondary data and selected by using purposive sampling method. Model analysis using linear regression analysis. This research using intervening variable detection analysis to see that the intervening variable has an effect to intervening variable independend and variable dependend.Based on analytical results shows that variable board size, board of director, institutional ownership don’t have significant influence toward intellectual capital, while variable board of independence and, managerial ownership have significant influence toward intellectual capital and the second results of this study is intellectual capital has a significant influence toward company performance.